Heuristic Optimization of Cooling Channel Design in the Hot Stamping Die for Hot Stamping Process - Mohd Fawzi, Zamri; A. R., Yusoff (Taylor & Francis, 2015)
In hot stamping process, similar die is used as in cold stamping process but with additional cooling channels. The cooling channel systems are integrated into the die design to control the cooling rate for quenching process of hot blanks. During quenching process, the die is effectively cooled to achieve the optimum cooling rate and homogeneous temperature distribution on hot blanks. In this paper, heuristic method with finite element analysis (FEA) of statis analysis and thermal analysis are applied to determine the cooling channel size, pitch size between channels and channel distance to the blanks surface. This static analysis identifies either the tool able to stand the pressure applied or not, while the thermal analysis is to ensure the die obtains the high cooling efficiency with homogenous temperature distribution. In this heuristic method, each parameter of the cooling channels inside the die are optimized and benchmarked with traditional Taguchi method. The results showed that the heuristic method coincides with Taguchi method even better and achieved the acceptance error between FEA in temperature distributions.